Evaluation of the effect of Irritrol as final irrigant against Staphylococcus epidermidis: an in Vitro Study. - Hezha Saadi Hassan; Diyar Khalid Bakr (Erbil Dental Journal)
Background and Objective: Endodontic infections are considered to be caused by the presence of various microorganisms within the root canal system. Staphylococcus epidermidis is one of the most isolated or detected species from oral infections, including marginal periodontitis, infected root canals, peri‐radicular, peri‐implantitis, and also detected in cases of failed endodontic therapy. In order to prevent endodontic treatment, failure irrigation is mandatory for the effective removal of smear, pulp tissue, smear layer,and microorganisms. The objective of the current study is to evaluate and compare the effect of Irritrol with other final irrigants regarding disinfecting root canal from S. epidermidis. Methods: Fifty‐five single roots premolars with single canals were selected. All of the samples were infected with standard strains of Staphylococcus Epidermidis. Samples were randomly divided into five groups, and five teeth were put as a control group to be compared to the samples after disinfection. Each group consisted of 10 samples according to the type of final irrigants used during and after instrumentation: 5.25% NaOCl/ Irritrol as final irrigant G2 NaOCl 5.25% / NaOCl 5.25%, G3 Normal Saline, G4 Irritrol with activation, G5 NaOCl with activation. All samples were prepared and instrumented by using ProTaper NEXT rotary system till X3. 5.25% NaOCl was applied with a 27‐G double side‐vented syringe needle as an initial irrigant then followed by the final irrigants. Ultra X ultrasonic device was used for the activation of irrigation with a high degree of 45,000 kHz and using tip size 20# with taper of 2%. CFU of each sample was counted before irrigation regime and after the irrigation regime, and they were compared to the control group. Results: In decreasing the amount of bacteria colonies G4 (Irritol with activation) 94% and G5 (NaOCl 5.25%), 92% of the CFU were decreased compared to the control group. Whereas, in Group 3 (Normal Saline) had the least effect on the CFU count decrease. In group 1 (Irritrol) and G2 without activation. Irritrol had less effect than NaOCl 5.25% in the amount of eliminating bacteria count. Conclusion: Irritrol, NaOCl 5.25% with the aid of PUI, can eliminate a significant amount of bacteria in the root canal. In the future, irritrol might be able to be a promising antibacterial irrigant as well as a chelating agent.